2023
DOI: 10.3934/gf.2023010
|View full text |Cite
|
Sign up to set email alerts
|

Does corporate reputation play a mediating role in the association between manufacturing companies' corporate social responsibility (CSR) and financial performance?

Abstract: <abstract> <p>The main objective of this research was to analyze the variable of corporate reputation as a mediating variable to determine the relationship between corporate social responsibility and financial performance. Simple random sampling was used in the study to obtain 300 respondents from Bangladeshi manufacturing companies. Statistical Package for the Social Sciences (SPSS) 23.0 was used to analyze the data. To evaluate the hypotheses in this study, structural equation modeling (SEM) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…As the main engine of national economic development, industrial enterprises generate high GDP growth while causing numerous negative impacts for the ecological environment [77]. Corporate social responsibility is seen as necessary to enable businesses to satisfy the demands of changing times and achieve sustainable growth [78] (p. 243). In this competitive world, every nation tries to acquire sustainable economic solvency.…”
Section: Discussionmentioning
confidence: 99%
“…As the main engine of national economic development, industrial enterprises generate high GDP growth while causing numerous negative impacts for the ecological environment [77]. Corporate social responsibility is seen as necessary to enable businesses to satisfy the demands of changing times and achieve sustainable growth [78] (p. 243). In this competitive world, every nation tries to acquire sustainable economic solvency.…”
Section: Discussionmentioning
confidence: 99%
“…At the micro level, many enterprises are gradually beginning green transformation and engaging in green finance; thus, green transformation may also affect corporate finance. Enterprises’ contributions to environmental protection play a vital role in corporate social responsibility and positively impact corporate reputation and financial performance [ 46 ]. Additionally, Huang et al (2023) explore the effects of corporate size, degree of internationalization, profits, and competitiveness on the degree of engagement in green finance and find that corporate size is positively related to the degree of engagement in green finance [ 47 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Compared to other green financial instruments, green credit, and bonds are more widely used by enterprises; however, these instruments can significantly increase the debt financing scale [ 72 , 73 ]. Moreover, green technology transformation can enhance corporate reputation [ 46 ], which may affect business credit.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…By analyzing the data from 490 Chinese manufacturing firms, Luo et al (2022) concluded that CSR fosters sustainable financial performance. Jing et al (2023) examined the CSR and financial performance nexus with 300 respondents from Bangladesh manufacturing firms. Their findings demonstrated a positive link between these two variables.…”
Section: Csr and Financial Performancementioning
confidence: 99%